Wide-spread brain alterations early after the onset of Crohn’s disease in children in remission—a pilot study - Filip, Pavel; Vojtíšek, Lubomír; Jičínská, Anna Marie; Valenta, Zdeněk; Horák, Ondřej; Hrunka, Matěj; Mangia, Silvia; Michaeli, Shalom; Jabandžiev, Petr (Frontiers in Neuroscience, 2024)
BackgroundThe research on possible cerebral involvement in Crohn’s disease (CD) has been largely marginalized and failed to capitalize on recent developments in magnetic resonance imaging (MRI).ObjectiveThis cross-sectional pilot study searches for eventual macrostructural and microstructural brain affection in CD in remission and early after the disease onset.Methods14 paediatric CD patients and 14 healthy controls underwent structural, diffusion weighted imaging and quantitative relaxation metrics acquisition, both conventional free precession and adiabatic rotating frame transverse and longitudinal relaxation time constants as markers of myelination, iron content and cellular loss.ResultsWhile no inter-group differences in cortical thickness and relaxation metrics were found, lower mean diffusivity and higher intracellular volume fraction were detected in CD patients over vast cortical regions essential for the regulation of the autonomous nervous system, sensorimotor processing, cognition and behavior, pointing to wide-spread cytotoxic oedema in the absence of demyelination, iron deposition or atrophy.ConclusionAlthough still requiring further validation in longitudinal projects enrolling larger numbers of subjects, this study provides an indication of wide-spread cortical oedema in CD patients very early after the disease onset and sets possible directions for further research.